Back Cover: Defying Thermodynamics: Stabilization of Alane Within Covalent Triazine Frameworks for Reversible Hydrogen Storage (Angew. Chem. Int. Ed. 49/2021). Issue 49 (4th October 2021) - Stavila, Vitalie; Li, Sichi; Dun, Chaochao; Marple, Maxwell A. T.; Mason, Harris E.; Snider, Jonathan L.; Reynolds, Joseph E.; El Gabaly, Farid; Sugar, Joshua D.; Spataru, Catalin D.; Zhou, Xiaowang; Dizdar, Brennan; et al.
Abstract : A cluster of alane (AlH3 ) stabilized by coordination to nitrogen binding sites within the nanopores of a bipyridine‐functionalized covalent triazine framework, CTF‐bipy, is shown on the cover image. In their Research Article on page 25815, Vitalie Stavila, Mark D. Allendorf, and co‐workers demonstrate how the resulting AlH3 @CTF‐bipy material releases hydrogen at temperatures as low as 95 °C with full decomposition at 250 °C. The hydride can be regenerated at 60 °C under 700 bar hydrogen, a pressure that is more than an order of magnitude lower compared to that required to hydrogenate bulk aluminum.